KEBIJAKAN PEMERINTAH KABUPATEN TAPANULI SELATAN DALAM BIDANG PENDIDIKAN ISLAM: IMPLIKASI TERHADAP PENINGKATAN PEMAHAMAN MASYARAKAT TENTANG PENDIDIKAN AGAMA ISLAM - Rhama Lenasari; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
This study discusses the policies of the South Tapanuli Regency Government in the field of Islamic education and their implications for improving the public’s understanding of Islamic religious education. The problem addressed is how these policies are implemented and the extent of their influence on the community’s comprehension of Islamic education. The research method used is qualitative with a case study approach, involving interviews, observations, and documentation as data collection techniques. Data analysis is conducted descriptively and qualitatively to provide an in-depth description of the policies and their impacts. The results show that the policies implemented by the South Tapanuli Regency Government have made a positive contribution to increasing public awareness and understanding of Islamic religious education. However, there are several obstacles in the implementation that require attention to optimize the effectiveness of the policies. In conclusion, government policies play a strategic role in strengthening Islamic education and significantly influence the improvement of public understanding.